A two-dimensional non-lead perovskite material and its preparation method and application

By developing two-dimensional non-lead perovskite material (C18H35NH3) 2SnX4, the problems of poor toxicity of lead-based materials and poor stability of tin-based materials have been solved, and materials with high stability and good luminous properties have been achieved, suitable for optoelectronic devices, especially White light emitting device.

CN115710495BActive Publication Date: 2025-01-14FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110978054.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-23
Publication Date
2025-01-14
Estimated Expiration
2041-08-23

AI Technical Summary

Technical Problem

Lead-based perovskite materials are limited in commercial applications due to the toxicity of lead, and Sn(II) of tin-based materials are prone to oxidation, resulting in poor stability, which limits their development and application.

Method used

A two-dimensional non-lead perovskite material (C18H35NH3) 2SnX4, wherein X is Cl, Br, I or a mixture thereof, was developed to prepare materials with sheet-like structure and good stability, including tin sources, by specific synthetic methods. , organic amines, organic acids and halogen react at high temperatures, and the reaction conditions are controlled to obtain materials with different halogen ratios.

Benefits of technology

It has achieved higher stability and good luminous performance than three-dimensional tin halide perovskites. Materials with different luminous wavelengths can be used in white light emitting devices, with great development potential in the fields of luminous displays and optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115710495B_ABST
    Figure CN115710495B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of luminescent materials, and specifically relates to a two-dimensional non-lead perovskite material and a preparation method and application thereof. The molecular formula of the two-dimensional non-lead perovskite material is (C 18 H 35 NH3)2SnX4, wherein X is a halogen element selected from one, two or three of Cl, Br and I. The two-dimensional non-lead perovskite material of the present invention has good luminescent properties, and because the organic cation has a better protective effect on the photoactive tin halide structural unit, the two-dimensional tin halide perovskite exhibits higher stability than the three-dimensional tin halide perovskite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and specifically relates to a two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 S X 4 And its preparation method and application. Background Art

[0002] In recent years, lead-based perovskite materials have attracted extensive attention from researchers at home and abroad. Due to their excellent properties such as high light absorption coefficient, long carrier lifetime, and simple preparation process, these materials have shown good application prospects in optoelectronic devices such as solar cells, photodetectors, and light-emitting diodes. However, due to the toxicity of lead, its commercial application is limited.

[0003] In order to solve the toxicity problem of lead, the tin-based system of the same main group is currently considered. It has the characteristics of non-toxicity, electronic structure similar to lead, adjustable band gap, low exciton binding energy, etc. Non-toxic perovskite materials based on the tin-based system have been developed. Based on ASnI 3 [A=CH 3 NH 3 、CH(NH 2 ) 2 Three-dimensional perovskites based on Sn(II) or Cs] have been shown to be capable of being used in high-efficiency solar cells; however, their development and application are hampered by the fact that Sn(II) is easily oxidized and has poor stability. Summary of the invention

[0004] In order to improve the defects of the prior art, the present invention provides a two-dimensional non-lead perovskite material, whose molecular formula is (C 18 H 35 NH 3 ) 2 S X 4 , wherein X is a halogen element selected from one, two or three of Cl, Br and I.

[0005] Preferably, the (C 18 H 35 NH 3 ) 2 S X 4 For (C 18 H 35 NH 3 ) 2 SnCl 4 , (C 18 H 35 NH 3 ) 2 S N 4 , (C18 H 35 NH 3 ) 2 Sn 4 , (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 , (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 or (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 , wherein x1, x2, x3 are independently selected from 1, 2 or 3.

[0006] Preferably, the two-dimensional non-lead perovskite material is a sheet structure.

[0007] Preferably, the two-dimensional non-lead perovskite material is a micro-sheet structure stacked vertically together.

[0008] Preferably, the size of the two-dimensional non-lead perovskite material does not exceed 50 microns, preferably 0.1 to 20 microns, more preferably 0.1 to 10 microns, for example 0.1 micron, 0.5 micron, 1 micron, 2 microns.

[0009] According to an embodiment of the present invention, the two-dimensional non-lead perovskite material has substantially Figure 1 The electron microscope morphology is shown.

[0010] According to an embodiment of the present invention, the two-dimensional non-lead perovskite material has substantially Figure 2 XRD pattern shown.

[0011] According to an embodiment of the present invention, the two-dimensional non-lead perovskite material has substantially the following properties when irradiated with excitation light having a wavelength of 300-365 nm: Figure 3 Orange or red light emission shown.

[0012] Preferably, the (C 18 H 35 NH 3 ) 2 SnCl 4Under ultraviolet light excitation (eg, 300 nm), it emits orange light, for example, orange light with a wavelength of 616 nm.

[0013] Preferably, the (C 18 H 35 NH 3 ) 2 S N 4 Under ultraviolet light excitation (eg, 346 nm), there is orange light emission, for example, orange light emission with a wavelength of 619 nm.

[0014] Preferably, the (C 18 H 35 NH 3 ) 2 Sn 4 Under ultraviolet light excitation (eg, 365 nm), there is red light emission, for example, red light emission with a wavelength of 666 nm.

[0015] Preferably, the (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 Under ultraviolet light excitation (eg, 341 nm), there is orange light emission, for example, orange light emission with a wavelength of 624 nm.

[0016] Preferably, the (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 Under ultraviolet light excitation (eg, 365 nm), there is red light emission, for example, red light emission with a wavelength of 666 nm.

[0017] Preferably, the (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 Under ultraviolet light excitation (eg, 317 nm), it emits orange light with a wavelength of 642 nm.

[0018] According to an embodiment of the present invention, the two-dimensional non-lead perovskite material has substantially Figure 4 The monoexponential fluorescence decay lifetime is shown.

[0019] According to an embodiment of the present invention, the fluorescence quantum yield of the two-dimensional non-lead perovskite material is 1-90%, preferably 60-90%, for example 85%.

[0020] The present invention also provides a method for preparing the above-mentioned two-dimensional non-lead perovskite material, comprising the following steps:

[0021] 1) mixing a tin source, an organic amine, an organic acid and octadecene to obtain a mixed solution 1;

[0022] 2) adding a halogen source into the mixed solution 1 to react and obtain the two-dimensional non-lead perovskite material.

[0023] According to an embodiment of the present invention, in step 1), the molar volume ratio of the tin source to the organic amine is (0.02-0.5) mmol: (0.5-1.5) ml, preferably (0.1-0.4) mmol: (0.8-1.2) ml, for example 0.3 mmol: 1 ml.

[0024] According to an embodiment of the present invention, in step 1), the volume ratio of the organic amine, the organic acid and octadecene is (0.5-1.5):(0.5-1.5):(5-15), preferably (0.8-1.2):(0.8-1.2):(8-12), for example, 1:1:10.

[0025] According to an embodiment of the present invention, the molar ratio of the tin source to the halogen source is (0-2):(0-20) and does not include the value of 0, preferably (0.9-1):(2-15), for example, 0.9:2, 0.9:3, 0.9:4, 0.9:5, 0.9:6, 1:2, 1:3, 1:4, 1:5, 1:6, 0.95:6.

[0026] According to an embodiment of the present invention, the combined concentration of the tin source, the halogen source and the organic amine in the mixed solution 1 is no more than 25 mol%, preferably 5-20 mol%, more preferably 10-18 mol%, for example, the synthetic concentration is 13 mol%, 14 mol%, 17 mol%.

[0027] According to an embodiment of the present invention, the tin source is selected from one or a mixture of two or more of stannous oxalate, stannous octoate, stannous oxide, tin acetate and dibutyltin, for example, stannous octoate.

[0028] According to an embodiment of the present invention, the organic amine is R 1 NH 2 , wherein the R 1 Selected from C 4-22 A straight or branched alkyl group, preferably selected from C 4-20 A straight or branched chain alkyl group, more preferably, selected from C4-18 The straight-chain or branched-chain alkyl group may be, for example, one or a mixture of two or more of butylamine, n-octylamine, dodecylamine, octadecylamine and oleylamine, for example, oleylamine.

[0029] According to an embodiment of the present invention, the organic acid is R 2 COOH, wherein the R 2 Selected from C 6-20 A straight or branched alkyl group, preferably selected from C 7-17 The linear or branched alkyl group is, for example, octanoic acid, lauric acid, or oleic acid, or a mixture of two or more thereof, for example, oleic acid.

[0030] According to an embodiment of the present invention, the halogen source is selected from one, two or three of hydrochloric acid, hydrobromic acid and hydroiodic acid, preferably hydroiodic acid, hydrochloric acid or hydrobromic acid.

[0031] According to an embodiment of the present invention, the mixing in step 1) is performed under an inert atmosphere and heating conditions. Preferably, the inert atmosphere is achieved by introducing nitrogen and / or argon, such as nitrogen.

[0032] According to an embodiment of the present invention, the mixing temperature in step 1) is 80-200°C, preferably, the mixing temperature is 100-150°C, exemplified by 110°C, 120°C, 130°C, 140°C.

[0033] Preferably, the mixing in step 1) is performed under stirring conditions.

[0034] According to an embodiment of the present invention, before heating to 80-200° C. in step 1), the step further includes introducing nitrogen into the reaction raw materials and stirring for 10-30 minutes.

[0035] Preferably, the mixing time after heating is 0.5-1.5 hours, preferably 1-1.2 hours, for example 1 hour.

[0036] According to an embodiment of the present invention, after the reaction of the halogen source and the mixed solution 1 in step 2) is completed, a rapid cooling step is also included.

[0037] According to an embodiment of the present invention, the step 2) includes the following steps: adding a halogen source to the mixed solution 1 and reacting until complete, and then rapidly cooling to obtain the two-dimensional non-lead perovskite material.

[0038] Preferably, hydrochloric acid is added to the mixed solution 1 for reaction, and after the reaction is completed, rapid cooling is performed to obtain the two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 SnCl4 .

[0039] Preferably, hydrobromic acid is added to the mixed solution 1 for reaction, and after the reaction is completed, rapid cooling is performed to obtain the two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 S N 4 .

[0040] Preferably, hydroiodic acid is added to the mixed solution 1 for reaction, and after the reaction is completed, rapid cooling is performed to obtain the two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 Sn 4 .

[0041] Preferably, a mixture of hydrochloric acid and hydrobromic acid is added to the mixed solution 1 for reaction, and after the reaction is completed, rapid cooling is performed to obtain the two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 .

[0042] Preferably, a mixture of hydrochloric acid and hydroiodic acid is added to the mixed solution 1 for reaction, and after the reaction is completed, rapid cooling is performed to obtain the two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 .

[0043] Preferably, a mixture of hydroiodic acid and hydrobromic acid is added to the mixed solution 1 for reaction, and after the reaction is completed, rapid cooling is performed to obtain the two-dimensional non-lead perovskite material (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 .

[0044] According to an embodiment of the present invention, in the step 2), the temperature of the mixed solution 1 reacting with the halogen source is 150-250°C, preferably 160-220°C, for example 200°C.

[0045] Among them, since the volume of the halogen source is very small, the temperature of the mixed solution 1 will quickly reach the same temperature as that of the mixed solution 1 after it is added. Therefore, the temperature of the reaction in step 2) is the same as that of the mixed solution 1.

[0046] Preferably, in step 2), the reaction time of the halogen source and the mixed solution 1 is 5-100 seconds, for example, 10-60 seconds.

[0047] According to an embodiment of the present invention, the step 2) is carried out under an inert atmosphere and stirring conditions.

[0048] Preferably, the rapid cooling comprises cooling the reacted solution to room temperature in an ice water bath.

[0049] According to an embodiment of the present invention, the step 2) further comprises the step of separating and purifying the reaction product after the rapid cooling. Preferably, the separation is carried out under centrifugal conditions.

[0050] As an embodiment, the step 2) includes the following steps: heating the mixed solution 1 to 180-250° C., adding a halogen source, reacting for 5-60 seconds under an inert atmosphere and stirring, cooling the reaction solution to room temperature in an ice water bath, centrifuging and purifying to obtain the two-dimensional non-lead perovskite material.

[0051] The present invention also provides the use of the two-dimensional non-lead perovskite material in light-emitting displays and optoelectronic devices.

[0052] The present invention also provides the above (C 18 H 35 NH 3 ) 2 S N 4 The application of two-dimensional non-lead perovskite materials in the field of light-emitting displays and optoelectronic devices is preferably used as the active light-emitting layer of white light-emitting devices.

[0053] The present invention also provides a method comprising the above (C 18 H 35 NH 3 ) 2 S N 4 An optoelectronic device of a two-dimensional non-lead perovskite material; preferably, the optoelectronic device is a white light emitting device.

[0054] Beneficial Effects

[0055] The present invention provides a two-dimensional non-lead perovskite luminescent material: (C 18 H 35 NH 3 ) 2 SnCl 4 , (C 18 H 35NH 3 ) 2 S N 4 , (C 18 H 35 NH 3 ) 2 Sn 4 , (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 , (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 and (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 , has good luminescence properties, and because organic cations have a better protective effect on the photoactive tin halide structural units, the two-dimensional tin halide perovskite exhibits higher stability than the three-dimensional tin halide perovskite.

[0056] The present invention adopts a high-temperature hot injection method to prepare the two-dimensional non-lead perovskite luminescent material, the synthesis conditions are easy to control, the repeatability is good, and the prepared two-dimensional non-lead perovskite luminescent material has good dispersibility and repeatability; the method of the present invention effectively regulates the band gap of the two-dimensional non-lead perovskite luminescent material by changing the halogen source, and finally prepares (C 18 H 35 NH 3 ) 2 SnCl 4 , (C 18 H 35 NH 3 ) 2 S N 4 , (C 18 H 35 NH 3 ) 2 Sn 4 , (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 , (C 18H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 and (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 Two-dimensional non-lead perovskite luminescent material. 18 H 35 NH 3 ) 2 S N 4 It has good luminescence performance and can be used as the active luminescent layer of white light emitting devices. It has great development potential in the fields of luminescent display and optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 is a low-resolution transmission electron micrograph of the two-dimensional non-lead perovskite luminescent material of the present invention, wherein (a) is (C) in Example 1 18 H 35 NH 3 ) 2 SnCl 4 (a) is a low-resolution transmission electron microscopy image (scale is 2 μm), (b) is a low-resolution transmission electron microscopy image (scale is 2 μm) of Example 2 (C 18 H 35 NH 3 ) 2 S N 4 (c) is a low-resolution transmission electron microscopy image (scale is 0.5 μm) of Example 3 (C 18 H 35 NH 3 ) 2 Sn 4 Low-resolution transmission electron microscopy image (scale bar: 0.5 μm).

[0058] Figure 2 For Example 1 (C 18 H 35 NH 3 ) 2 SnCl 4 , in Example 2 (C 18 H 35 NH 3 ) 2 S N 4 , in Example 3 (C 18 H 35 NH 3 ) 2 Sn4 X-ray powder diffraction pattern of .

[0059] Figure 3 For Example 1 (C 18 H 35 NH 3 ) 2 SnCl 4 , in Example 2 (C 18 H 35 NH 3 ) 2 S N 4 , in Example 3 (C 18 H 35 NH 3 ) 2 Sn 4 , in Example 4 (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 , in Example 5 (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 and Example 6 (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 Emission spectra under UV excitation at different wavelengths.

[0060] Figure 4 In Example 1 (C 18 H 35 NH 3 ) 2 SnCl 4 , in Example 2 (C 18 H 35 NH 3 ) 2 S N 4 , in Example 3 (C 18 H 35 NH 3 ) 2 Sn 4 , in Example 4 (C 18 H 35 NH 3 ) 2 Sn(Clx1 Br 1-x1 ) 4 , in Example 5 (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 and Example 6 (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 Fluorescence lifetime diagram of the material under OPO laser excitation. DETAILED DESCRIPTION

[0061] The material of the present invention and its preparation method and application will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only for exemplary description and explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0062] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0063] In this example, the following instruments and conditions were used to test the compounds:

[0064] The instrument model of the low-resolution transmission electron microscope is JEM-2010, and the manufacturer is JEOL.

[0065] The instrument model of the X-ray powder diffractometer is MiniFlex2, the manufacturer is Rigaku, and the radiation wavelength of the copper target is λ=0.154187 nm.

[0066] The instrument model of the fluorescence spectrometer is FLS980, the manufacturer is Edinburgh, and the excitation light source is a xenon lamp.

[0067] The instrument model of the steady-state transient fluorescence phosphorescence spectrometer is FLS980, the manufacturer is Edinburgh, and the excitation light source is OPO laser.

[0068] Example 1

[0069] (C 18 H 35 NH 3 ) 2 SnCl 4 Preparation

[0070] At room temperature, oleylamine, oleic acid and octadecene in a volume ratio of 1:1:10 were transferred to a double-necked round-bottom flask, 0.3 mmol of stannous octoate was added under an inert atmosphere, and the mixture was heated to 120°C and stirred for dissolution reaction for 1 hour to obtain a mixed solution 1. The mixed solution 1 was heated to 180°C, 350 μL of hydrochloric acid was quickly injected, and after reacting for 60 seconds, it was placed in an ice water bath and quickly cooled to room temperature, and centrifuged to obtain (C 18 H 35 NH 3 ) 2 SnCl 4 product.

[0071] See also Figure 1 As shown in (a), the product of this embodiment (C 18 H 35 NH 3 ) 2 SnCl 4 It has a flake structure with a size of about 1 μm. Its X-ray powder diffraction pattern is shown in Figure 2 .

[0072] like Figure 3 As shown, under 300nm ultraviolet light excitation, the (C 18 H 35 NH 3 ) 2 SnCl 4 The two-dimensional perovskite material exhibits orange light (616nm) emission.

[0073] See also Figure 4 It can be seen that the (C 18 H 35 NH 3 ) 2 SnCl 4 The τ of the two-dimensional perovskite material is 8.6μs (100%).

[0074] Example 2

[0075] (C 18 H 35 NH 3 ) 2 S N 4 Preparation of materials

[0076] At room temperature, oleylamine, oleic acid and octadecene in a volume ratio of 1:1:10 were transferred to a double-necked round-bottom flask, 0.3 mmol of stannous octoate was added under an inert atmosphere, and the mixture was heated to 120°C and stirred for dissolution reaction for 1 hour to obtain a mixed solution 1. The mixed solution 1 was heated to 200°C, 280 μL of hydrobromic acid was quickly injected, and after reacting for 60 seconds, it was placed in an ice water bath and quickly cooled to room temperature, and purified by centrifugation to obtain (C18 H 35 NH 3 ) 2 S N 4 product.

[0077] See also Figure 1 As shown in (b), the product of this embodiment (C 18 H 35 NH 3 ) 2 S N 4 It has a flake structure with a size of about 1 μm. Its X-ray powder diffraction pattern is shown in Figure 2 .

[0078] like Figure 3 As shown, under 346nm ultraviolet light excitation, the (C 18 H 35 NH 3 ) 2 S N 4 The two-dimensional perovskite material exhibits orange light (619nm) emission.

[0079] See also Figure 4 It can be seen that the (C 18 H 35 NH 3 ) 2 S N 4 The τ of the two-dimensional perovskite material is 4.0 μs (100%).

[0080] Example 3

[0081] (C 18 H 35 NH 3 ) 2 Sn 4 Preparation of materials

[0082] At room temperature, oleylamine, oleic acid and octadecene in a volume ratio of 1:1:10 were transferred to a double-necked round-bottom flask, 0.3 mmol of stannous octoate was added under an inert atmosphere, and the mixture was heated to 120°C and stirred for dissolution reaction for 1 hour to obtain a mixed solution 1. The mixed solution 1 was heated to 200°C, 300 μL of hydroiodic acid was quickly injected, and after reacting for 60 seconds, it was placed in an ice-water bath and quickly cooled to room temperature, and purified by centrifugation to obtain (C 18 H 35 NH 3 ) 2 Sn 4 product.

[0083] See Figure 1 As shown in (c), the product of this embodiment (C 18 H35 NH 3 ) 2 Sn 4 It is in flake form, about 1 μm in size, and its X-ray powder diffraction pattern is shown in Figure 2 .

[0084] like Figure 3 As shown, under 365nm ultraviolet light excitation, this embodiment obtains (C 18 H 35 NH 3 ) 2 Sn 4 The two-dimensional perovskite material exhibits red light (666nm) emission.

[0085] See also Figure 4 It can be seen that the (C 18 H 35 NH 3 ) 2 Sn 4 The τ of the two-dimensional perovskite material is 1.2μs (100%).

[0086] Example 4

[0087] (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 Preparation of materials

[0088] At room temperature, oleylamine, oleic acid and octadecene in a volume ratio of 1:1:10 were transferred to a double-necked round-bottom flask, 0.3 mmol of stannous octoate was added under an inert atmosphere, and the mixture was heated to 120°C and stirred for dissolution reaction for 1 hour to obtain a mixed solution 1. The mixed solution 1 was heated to 200°C, 175 μL of hydrochloric acid and 140 μL of hydrobromic acid were quickly injected, and the mixture was reacted for 60 seconds and then placed in an ice water bath and quickly cooled to room temperature, and centrifuged to obtain (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 Product, calculated based on the halogen feed ratio, x1=0.62.

[0089] like Figure 3 As shown, under 341nm ultraviolet light excitation, the (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br1-x1 ) 4 The two-dimensional perovskite material exhibits orange light (624nm) emission.

[0090] See also Figure 4 It can be seen that the (C 18 H 35 NH 3 ) 2 Sn(Cl x1 Br 1-x1 ) 4 The τ of the two-dimensional perovskite material is 4.3μs (100%).

[0091] Example 5

[0092] (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 Preparation of materials

[0093] At room temperature, oleylamine, oleic acid and octadecene in a volume ratio of 1:1:10 were transferred to a double-necked round-bottom flask, 0.3 mmol of stannous octoate was added under an inert atmosphere, and the mixture was heated to 120°C and stirred for 1 hour to obtain a mixed solution 1. The mixed solution 1 was heated to 200°C, 175 μL of hydrochloric acid and 150 μL of hydroiodic acid were quickly injected, and the mixture was reacted for 60 seconds and then placed in an ice-water bath and quickly cooled to room temperature, and centrifuged to obtain (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 Product, calculated based on the halogen feed ratio, x2=0.61.

[0094] like Figure 3 As shown, under 365nm ultraviolet light excitation, the (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I 1-x2 ) 4 The two-dimensional perovskite material exhibits red light (666nm) emission.

[0095] See also Figure 4 It can be seen that the (C 18 H 35 NH 3 ) 2 Sn(Cl x2 I1-x2 ) 4 The τ of the two-dimensional perovskite material is 1.2μs (100%).

[0096] Example 6

[0097] (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 Preparation of materials

[0098] At room temperature, oleylamine, oleic acid and octadecene in a volume ratio of 1:1:10 were transferred to a double-necked round-bottom flask, 0.3 mmol of stannous octoate was added under an inert atmosphere, and the mixture was heated to 120°C and stirred for 1 hour to obtain a mixed solution 1. The mixed solution 1 was heated to 200°C, and 140 μL of hydrobromic acid and 150 μL of hydroiodic acid were quickly injected. After reacting for 60 seconds, the reaction solution was quickly cooled to room temperature in an ice water bath, and purified by centrifugation to obtain (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 Product, calculated on the basis of halogen feed ratio, x3=0.49.

[0099] like Figure 3 As shown, under 317nm ultraviolet light excitation, the (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 The two-dimensional perovskite material exhibits orange light (642nm) emission.

[0100] See also Figure 4 It can be seen that the (C 18 H 35 NH 3 ) 2 Sn(Br x3 I 1-x3 ) 4 The τ of the two-dimensional perovskite material is 0.8μs (100%).

[0101] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a two-dimensional non-lead perovskite material, comprising the following steps: 1) mixing stannous octoate, oleylamine, oleic acid and octadecene at 80-200° C. in an inert atmosphere for 0.5-1.5 hours to obtain a mixed solution 1; 2) adding a halogen source to the mixed solution 1 and reacting at a temperature of 150-250° C. for 5-100 seconds, and then rapidly cooling to obtain the two-dimensional non-lead perovskite material; The halogen source is selected from one, two or three of hydrochloric acid, hydrobromic acid and hydroiodic acid; The molecular formula of the two-dimensional non-lead perovskite material is (C 18 H 35 NH3)2SnCl4, (C 18 H 35 NH3)2SnBr4、(C 18 H 35 NH3)2SnI4、(C 18 H 35 NH3)2Sn(Cl x1 Br 1-x1 )4、(C 18 H 35 NH3)2Sn(Cl x2 I 1-x2 )4 or (C 18 H 35 NH3)2Sn(Br x3 I 1-x3 )4, wherein x1, x2, x3 are independently selected from 1, 2 or 3.

2. The method for preparing a two-dimensional non-lead perovskite material according to claim 1, characterized in that: In the step 2), the combined concentration of stannous octoate, the halogen source and the organic amine is no more than 25 mol %.

3. The method for preparing a two-dimensional non-lead perovskite material according to any one of claims 1 to 2, characterized in that: The rapid cooling includes cooling the reacted solution to room temperature in an ice water bath.

4. A two-dimensional non-lead perovskite material prepared by the method according to any one of claims 1 to 3, characterized in that: The molecular formula of the two-dimensional non-lead perovskite material is (C 18 H 35 NH3)2SnCl4, (C 18 H 35 NH3)2SnBr4、(C 18 H 35 NH3)2SnI4、(C 18 H 35 NH3)2Sn(Cl x1 Br 1-x1 )4、(C 18 H 35 NH3)2Sn(Cl x2 I 1-x2 )4 or (C 18 H 35 NH3)2Sn(Br x3 I 1-x3 )4, wherein x1, x2, x3 are independently selected from 1, 2 or 3.

5. The two-dimensional non-lead perovskite material according to claim 4, characterized in that: The two-dimensional non-lead perovskite material is a sheet structure.

6. The two-dimensional non-lead perovskite material according to claim 4, characterized in that: The two-dimensional non-lead perovskite material has an XRD spectrum as shown in FIG. 2 .

7. Use of the two-dimensional non-lead perovskite material prepared by the method of any one of claims 1 to 3 or the two-dimensional non-lead perovskite material according to any one of claims 4 to 6 in light-emitting displays and optoelectronic devices.

8. The use according to claim 7, characterized in that The two-dimensional non-lead perovskite material is used as an active light-emitting layer of a white light-emitting device.

9. An optoelectronic device, comprising a two-dimensional non-lead perovskite material prepared by the method of any one of claims 1 to 3 or a two-dimensional non-lead perovskite material according to any one of claims 4 to 6.

10. The optoelectronic device according to claim 9, characterized in that The optoelectronic device is a white light emitting device.